Optimization of Cinnamon Planting Density in Coconut Intercropping System in India - Subramanian Periasamy; null Surekha; Ravi Bhat; Anok Uchoi (Scientifica)
The study aimed to explore the potential of cinnamon intercropping as a vertical expansion strategy with increased planting density to increase cinnamon production and address the surge in global demand for this valuable spice crop. Despite lower individual plant quill yield, the high-density pentagonal method at 0.6 m × 1.2 m spacing with 7290 plant population h−1a resulted in high yield of 632 and 979 kg of cinnamon per hectare during first and second harvests, respectively, outperforming the control spacing (2.0 m × 2.0 m, 1404 population ha−1). Furthermore, the coconut + cinnamon intercropping system with spacing of 0.6 m × 1.2 m resulted in significantly higher system productivity of coconut equivalent yield of 55,766 nuts per hectare per year (average of two years) compared to other spacing treatments, showcasing its potential for enhanced cultivation and productivity. Therefore, the study concluded that cinnamon is a promising and economically feasible intercrop in coconut plantations when planted using the high-density pentagonal planting method with a closer spacing of 0.6 m × 1.2 m with 7290 plant population ha−1.